ANALISIS PERAN PEMERINTAH DALAM MEMBERIKAN PEMENUHAN HAK PEKERJAAN BAGI PENYANDANG DISABILITAS - marsitadewi, Komang ema (JPAP: Jurnal Penelitian Administrasi Publik, 2022)
Persons with disabilities are a group that often gets discriminated against in various rights. One of them is the right to get a job. The role of the government is very much needed by people with disabilities so that the rights of people with disabilities can be fulfilled. The size of the government’s role will greatly affect the extent to which the rights of persons with disabilities can be fulfilled. Therefore, this study analyzes the role of the government in providing fulfillment of work rights for Persons with Disabilities in Yogyakarta City and Denpasar City. The method used in this study is a qualitative research method. This study describes the problem of fulfilling the employment rights of persons with disabilities with different loci, namely in Yogyakarta and Denpasar. Based on the results of the analysis of the government’s role, the activities carried out by both the Denpasar City Government and the Yogyakarta City Government are almost the same, namely providing training to people with disabilities, outreach to job providers and connecting people with disabilities with job providers which are still done manually. Recommendations for the government to provide more training to persons with disabilities in accordance with the current needs of persons with disabilities.